What If?: Serious Scientific Answers to Absurd Hypothetical Questions - Randall Munroe (John Murray, 2015)
Science's most intriguing questions answered by the web's favourite writer, the genius behind xkcd.com. Munroe's hilarious and compelling answers explain everything from the odds of meeting your one true soulmate to how many humans a rampaging T-Rex would need to eat a day.